2004
DOI: 10.1002/gps.1145
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Care Mapping reconsidered: exploring the reliability and validity of the observational tool

Abstract: Questions were raised regarding the reliability and validity of DCM as used by routine care staff. Possible reasons for this, and suggestions for amendments are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 12 publications
5
39
0
5
Order By: Relevance
“…As shown in Table 3, higher WIB scores are associated with being more cognitively intact, non-agitated, non-depressed, and socially engaged, relationships that have been reported previously (Brooker et al, 1998;Chung, 2004;Edelman et al, 2004;Kuhn et al, 2004;Thornton et al, 2004). However, such a relationship is not unique to DCM, but is characteristic of many QOL measures (Sloane et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
“…As shown in Table 3, higher WIB scores are associated with being more cognitively intact, non-agitated, non-depressed, and socially engaged, relationships that have been reported previously (Brooker et al, 1998;Chung, 2004;Edelman et al, 2004;Kuhn et al, 2004;Thornton et al, 2004). However, such a relationship is not unique to DCM, but is characteristic of many QOL measures (Sloane et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
“…Dementia Care Mapping has significant value for assessing person-centered care from a proxy view of nursing home residents who have dementia. However, there are concerns about its resource intensive nature (Fossey, Lee, & Ballard, 2002;Sloane et al, 2007;Thornton, Hatton, & Tatham, 2004) and the reliability and validity of the instrument (Chenoweth & Jeon, 2007;Sloane et al, 2007;Thornton et al, 2004). Although Dementia Care Mapping has grown in popularity for use with long-term care residents in many European countries (Fulton, Edelman, & Kuhn, 2006), this assessment method is not an efficient means of assessing person-centered care and is inppropriate for persons who do not have moderate to severe dementia.…”
Section: Introductionmentioning
confidence: 99%
“…DCM has been criticised for being a complex tool and studies have, therefore, suggested a lack of coding consistency between mappers is of concern, raising concerns about the potential usefulness DCM data as a robust evidence-based measure of care quality or quality of life (19). DCM guidance (2) recommends that mappers establish inter-rater reliability (IRR) (minimum 70% concordance across BCC and ME values) with any co-mapper ahead of use, and that every mapper conduct an IRR map at least once per year.…”
Section: Dementia Care Mappingmentioning
confidence: 99%
“…DCM guidance (2) recommends that mappers establish inter-rater reliability (IRR) (minimum 70% concordance across BCC and ME values) with any co-mapper ahead of use, and that every mapper conduct an IRR map at least once per year. Published literature highlights that while a number of research studies have examined IRR and demonstrated it can be established effectively between experienced mappers in research contexts (10,20), relatively little is really known about IRR between mappers in everyday practice or whether IRR checks are completed regularly (19). In one study, Thornton et al examined IRR in the context of everyday mapping.…”
Section: Dementia Care Mappingmentioning
confidence: 99%